Fluid identification in tight sandstone reservoirs based on a new rock physics model. (15th July 2016) - Sun, Jianmeng; Wei, Xiaohan; Chen, Xuelian
Abstract: To identify pore fluids, we establish a new rock physics model named the tight sandstone dual-porosity model based on the Voigt–Reuss–Hill model, approximation for the Xu–White model and Gassmann's equation to predict elastic wave velocities. The modeling test shows that predicted sonic velocities derived from this rock physics model match well with measured ones from logging data. In this context, elastic moduli can be derived from the model. By numerical study and characteristic analyzation of different elastic properties, a qualitative fluid identification method based on Poisson's ratio and the S – L dual-factor method based on synthetic moduli is proposed. Case studies of these two new methods show the applicability in distinguishing among different fluids and different layers in tight sandstone reservoirs.